Quality evaluation of entrepreneurship education in higher education based on CIPP model and AHP-FCE methods - Fan, Xinqiao; Tian, Siyu; Lu, Zhenglan; Cao, Yirong (Frontiers in Psychology, 2022)
Entrepreneurship education has become an important component of higher education development. The purpose of this study is to evaluate entrepreneurship education and determine the extent of satisfaction with the education program. Firstly, based on the CIPP model, this article theoretically analyzes the factors affecting the quality of entrepreneurship education in colleges and universities, and clarifies the keys to improve that education quality. On this basis, using analytic hierarchy process (AHP) and fuzzy comprehensive evaluation (FCE) method, the evaluation index system and fuzzy evaluation model of entrepreneurial education are established. The results show that student participation is the most important factor affecting the quality of entrepreneurship education. Empirical analysis indicates that students have the highest satisfaction with teachers and the lowest satisfaction with the entrepreneurial environment. Apart from convenient and effective measurement of entrepreneurship education, the proposed model provides an important reference for improving the quality of entrepreneurship education in colleges and universities.